(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Kounis syndrome is an underdiagnosed clinical entity characterized by the concurrence of acute coronary syndrome with an allergic or hypersensitivity reaction. The inflammatory mediators released during an allergic reaction can induce coronary vasospasm or myocardial injury, making diagnosis and management particularly challenging. Case Presentation: We report the case of a 31-year-old female with a known history of multiple drug allergies who developed an anaphylactic reaction shortly after ingestion of levofloxacin prescribed for acute pharyngitis. Although her allergic symptoms improved following standard anaphylaxis management, she continued to experience persistent chest tightness. Electrocardiography revealed ischemic changes, and serial troponin I measurements demonstrated a marked elevation with a rising trend, confirming acute myocardial injury. In the absence of conventional cardiovascular risk factors, a diagnosis of Type I Kounis syndrome was established. Conclusion: This case highlights the importance of considering Kounis syndrome in patients presenting with chest pain during allergic reactions. Early electrocardiographic monitoring and serial cardiac biomarker assessment are essential for timely diagnosis and appropriate management, which may be lifesaving.